Поняття інформаційного освітнього простору як педагогічна проблема - Шахіна, Ірина Юріївна (НТУ "ХПІ", 2013)
У статті проаналізовано поняття інформаційного освітнього середовища, висвітлено роль Інтернету та засобів ІКТ у процесі формування ІОС, окреслено можливості функціонування та типи інформаційних освітніх середовищ.

The article deals with the concept of the information educational environment, the role of the Internet and the facilities of information communication technologies (ICT) in forming of information educational environment (IEE) is specified, the possibilities of functioning and the types of the information educational environments are described.
The information educational environment as a pedagogical problem
Keywords: технології інформаційно-комунікаційні; Інтернет; інформатизація; informative educational environment; Internet; informatively communicational technologies